Ryzyko informatyczne w działalności bankowej - Wawrzyniak, Dariusz (Information Risk Management in Banking, 2005)
The paper presents chosen aspects of information risk in banking. General ideas concerning the problem were described using the Basel Committee documents as well as NBP recommendations. The electronic banking security threats were presented as the crucial factors concerning information risk management. In addition the paper points to the role of non-technical aspects of risk management and information security management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 132-139